Sortimentos de eucalipto na região Centro-Oeste de Mato Grosso - Santos, Martha Aguiar dos (2019)
Forest managers are currently seeking increasingly profitable alternatives to forestry activities, such as the quantification and qualification of the volume and timber products that enable the prediction of multiple uses of the same, enabling and adding significant value to products from the forest. In this scenario, the objective of the work was to describe the profile of the stem and calculate the assortments of the hybrid Eucalyptus grandis W. Hill x Eucalyptus urophylla S. T. Blake, for optimization of the timber on the intent of better use of the stem from those trees on Midwest region of Mato Grosso. The database was composed of 270 trees cubed by the Smalian method and covering diameter between 6.0 cm and 40.0 com in DAP (diameter at 1.30 m), aged between 5 and 12 years, of seminal and clonal origin. Six taper function were studied at the level of stands and for data stratified in genetic material and in DAP classes. The accuracy of the estimates of the diameters along the shaft was compared as a function of the coefficient of determination, standard error of the estimate, of the Akaike Information Criterion, the Bayesian Information Criterion and the residue graph. And to evaluate the accuracy of commercial and partial volume estimates, the graphical analysis of the residuals, standard error of the percentage estimate and the Akaike Information Criterion were used. In addition, five classes of wood assortments were determined: energy; fence post; sawmill 1; sawing 2 and lamination. Calculations of the assortments were done through the FlorExel® Program. Based on the statistical criteria of evaluation of the estimated results, it was observed that the Kozak (1988) function is more suitable for taper studies when there is no stratification in the database. Through the model identity test it was verified that it is not recommended to fit a single equation the total set of data. In diametric class stratification, the function of Clark III et al. (1991) is indicated for class 1. Max and Burkhart (1976) is indicated for the classes of 1 to 5 and Schöpfer (1966) for class 6. In stratification by genetic material, the Clark III et al. (1991) is indicated for the clonal material and Kozak (1988) for the seminal. The equation of Clark III et al. (1991) is indicated to estimate the commercial volume when not stratified. In partial volume estimates, errors increased with increasing heights. In the clonal settlement, the assortment with the highest volume is post fence and in the seminal settlement is the lamination and the sawmill 1. The study revealed the potential of stands for the destination of noble products, such as sawing and rolling. Through the assortment table the evolution of the assortment within the diametric xvi classes was verified, being that individuals with larger dimensions present greater possibilities of diversifying their destination.